2017
DOI: 10.1159/000451078
|View full text |Cite
|
Sign up to set email alerts
|

Selective M2 Macrophage Depletion Leads to Prolonged Inflammation in Surgical Wounds

Abstract: Background: A prolonged inflammatory phase is seen in aberrant wound healing and in chronic wounds. Macrophages are central to wound healing. Distinct macrophage subtypes have differing roles both in initial inflammation and in later tissue repair. Broadly, these cells can be divided into M1 and M2 macrophages. M2 macrophage proliferation and differentiation is regulated by colony-stimulating factor 1 (CSF-1) signalling and can be blocked by GW2580, a competitive cFMS kinase inhibitor, thereby allowing for ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…This mirrors the results seen when both M1 and M2 phenotypes are depleted [ 24 , 25 , 26 ]. To further tease out the role of the M1 and M2 phenotypes, the cFMS kinase inhibitor GW2580 has been used to selectively inhibit the transition from M1 to M2 macrophages in an acute wound [ 31 ]. Blocking this transition prolongs the inflammatory phase; mice treated with this inhibitor prior to and during wound healing have higher number of neutrophils and macrophages at 14 days post injury compared to untreated mice [ 31 ].…”
Section: M2 Macrophages and Wound Closurementioning
confidence: 99%
See 1 more Smart Citation
“…This mirrors the results seen when both M1 and M2 phenotypes are depleted [ 24 , 25 , 26 ]. To further tease out the role of the M1 and M2 phenotypes, the cFMS kinase inhibitor GW2580 has been used to selectively inhibit the transition from M1 to M2 macrophages in an acute wound [ 31 ]. Blocking this transition prolongs the inflammatory phase; mice treated with this inhibitor prior to and during wound healing have higher number of neutrophils and macrophages at 14 days post injury compared to untreated mice [ 31 ].…”
Section: M2 Macrophages and Wound Closurementioning
confidence: 99%
“…To further tease out the role of the M1 and M2 phenotypes, the cFMS kinase inhibitor GW2580 has been used to selectively inhibit the transition from M1 to M2 macrophages in an acute wound [ 31 ]. Blocking this transition prolongs the inflammatory phase; mice treated with this inhibitor prior to and during wound healing have higher number of neutrophils and macrophages at 14 days post injury compared to untreated mice [ 31 ]. M2 macrophages secrete factors, such as TGF-β1, that induce the proliferation of fibroblasts and their differentiation into myofibroblasts.…”
Section: M2 Macrophages and Wound Closurementioning
confidence: 99%
“…Dysregulation of the shifting macrophage phenotypes during repair, leading for example to excessive production of pro‐inflammatory agents or deficient generation of proresolution macrophages, can produce defective repair or regeneration, chronic wounds, or excessive fibrosis and scarring (Wynn & Ramalingam, ). Studies of experimental injuries in diverse organs have shown that deleting macrophages at specific times during inflammation interferes with subsequent phases and leads to defective repair (Fiore et al, ; Klinkert et al, ; Perego et al, ). Of particular importance to regenerative biologists is the newer appreciation of the changing phenotypes of fibroblasts and other mesenchymal cells which orchestrate the onset of regeneration (Karin & Clevers, ; Nowarski et al., ).…”
Section: Roles Of Macrophages and Fibroblasts In Wound Repair And Regmentioning
confidence: 99%
“…Throughout inflammation and tissue repair in mammals, the activation states of resident macrophages and immigrating monocytes change to promote the tasks at hand, including angiogenesis, reformation of epithelial continuity, growth and differentiation of stem cells, and stimulation of widely ranging fibroblast activities. DAMP, damage-associated molecular pattern; PAMP, pathogen-associated molecular pattern; T reg cell, regulatory T cell; IRF5, interferon regulatory factor 5; NOS2, nitric oxide synthase 2; LXR, liver X receptor; AREG, amphiregulin; Arg1, arginase-1; IRF4, interferon regulatory factor 4; PPARg, peroxisome proliferator-activated receptor g; FGF, fibroblast growth factor; GAL-3, galectin-3; TGF, transforming growth factor; IC, immune complex; GR, glucocorticoid receptor; ATF3, activating transcription factor 3; SOCS, silencer of cytokine signaling have shown that deleting macrophages at specific times during inflammation interferes with subsequent phases and leads to defective repair (Fiore et al, 2016;Klinkert et al, 2017;Perego et al, 2016). Of particular importance to regenerative biologists is the newer appreciation of the changing phenotypes of fibroblasts and other mesenchymal cells which orchestrate the onset of regeneration (Karin & Clevers, 2016;Nowarski et al, 2017).…”
Section: Roles Of Macrophages and Fibroblasts In Wound Repair And Regmentioning
confidence: 99%
“…59,60 However, several pharmacological inhibitors to CSF1R or related kinases have been tested in clinical trials and overt immune system dysfunction was not found. More studies are needed to determine the potential systemic effect, including overall immune system function, of using a CSF1R inhibitor such as GW2580, including chronic animal models of PD such as synuclein mutation or overexpression.…”
mentioning
confidence: 99%